2001
DOI: 10.1046/j.1442-2042.2001.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of the latent period of bladder cancer in dyestuff‐plant workers in Japan

Abstract: Background: The carcinogenesis of benzidine (BZ) and beta-naphthylamine (BNA) for bladder is well known. Although it was thought to be rare to develop occupational bladder cancer more than 20 years after the exposure to these chemicals, there are still new clinical cases even 30 years after exposure. The purpose of this study was to re-evaluate the latent carcinogenic period of BZ and BNA, in order to set the safety period after exposure for the health surveillance system. Methods: The subjects were 236 dyestu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…[41][42][43][44] Second, exposure to benzidine and other arylamines has been associated with increased risks of bladder cancer in both Asian and Caucasian workers. 17,[45][46][47][48][49][50] Third, as shown in the metaanalysis presented in Table III of Asian populations not exposed to arylamines in the workplace, studies have shown that slow acetylation is a risk factor for bladder cancer comparable to the risk found in Caucasian populations, and the magnitude of the relative risk is the same. 3 Fourth, even though racial differences in the allele distribution among different ethnic groups have been reported, almost all of the alleles found in Caucasian groups have been described in Asian populations.…”
Section: Discussionmentioning
confidence: 93%
“…[41][42][43][44] Second, exposure to benzidine and other arylamines has been associated with increased risks of bladder cancer in both Asian and Caucasian workers. 17,[45][46][47][48][49][50] Third, as shown in the metaanalysis presented in Table III of Asian populations not exposed to arylamines in the workplace, studies have shown that slow acetylation is a risk factor for bladder cancer comparable to the risk found in Caucasian populations, and the magnitude of the relative risk is the same. 3 Fourth, even though racial differences in the allele distribution among different ethnic groups have been reported, almost all of the alleles found in Caucasian groups have been described in Asian populations.…”
Section: Discussionmentioning
confidence: 93%
“…A prospective study to demonstrate this effect would be both expensive and time consuming because of the long lag between exposure to carcinogens and the development of bladder cancer. 79 So-called 'secondary prevention' treats people with well-defined premalignant conditions to prevent the development of clinical cancer. As such premalignant disease states have not been generally recognized in bladder cancer, this approach has not been used in this disease.…”
Section: Implications For the Detection And Prevention Of Bladder Cancermentioning
confidence: 99%
“…During the first two time periods (1946–1965, 1966–1985), SIRs were elevated for men with the highest exposures. The latent period between date of hire and bladder cancer diagnosis (or death) were similar (19.5 and 24.1 years) and within the 15‐ to 40‐year range considered reasonable [Miyakawa et al, 2001]. Mean employment durations during the earlier two periods were also similar at 14.8 and 14.5 years, respectively.…”
Section: Discussionmentioning
confidence: 87%